2023
DOI: 10.3390/antibiotics12030584
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Aspergillosis in Humboldt Penguins—Susceptibility Patterns and Molecular Epidemiology of Clinical and Environmental Aspergillus fumigatus Isolates from a Belgian Zoo, 2017–2022

Abstract: Aspergillus fumigatus is the main causative agent of avian aspergillosis and results in significant health problems in birds, especially those living in captivity. The fungal contamination by A. fumigatus in the environment of Humboldt penguins (Spheniscus humboldti), located in a Belgian zoo, was assessed through the analysis of air, water, sand and nest samples during four non-consecutive days in 2021–2022. From these samples, potential azole-resistant A. fumigatus (ARAF) isolates were detected using a selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…39,40 Moreover, the extensive use of triazole antifungals has resulted in the emergence of azoleresistant A. fumigatus, which poses significant clinical and economic challenges. [41][42][43][44] Our study conducted in Ningxia province, China, observed an increase in the number of identified A. fumigatus strains from 2021 to 2023. Additionally, we discovered two azole-resistant strains during our research.…”
Section: Discussionmentioning
confidence: 84%
“…39,40 Moreover, the extensive use of triazole antifungals has resulted in the emergence of azoleresistant A. fumigatus, which poses significant clinical and economic challenges. [41][42][43][44] Our study conducted in Ningxia province, China, observed an increase in the number of identified A. fumigatus strains from 2021 to 2023. Additionally, we discovered two azole-resistant strains during our research.…”
Section: Discussionmentioning
confidence: 84%
“…It is difficult to interpret the outcomes of these studies, because sample background information is missing. A recent study reported azole resistance in 17.1% of clinical (6/35) and 11.8% (8/68) of environmental A. fumigatus isolates from Humboldt Penguins and other birds and their surroundings from 2017 to 2022 in a Belgian Zoo [ 32 ]. In this study sequencing of the cyp51A gene revealed the TR 34 /L98H mutation in all environmental isolates and TR 34 /L98H (2/6), F46Y/M172V/E427K (1/6) and the absence of known resistance mutations (3/6) in clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Despite not being drug-resistant, the outbreak still resulted in 21 infections and 9 deaths, in a population of only 211. A known opportunistic pathogen of penguins [ 25 ], azole drug-resistant A. fumigatus has been isolated from a zoo environment and from Humboldt penguins themselves [ 26 ]. However, little research is dedicated to the impact of aspergillosis on wildlife species in terms of clinical outcome and treatment failure, certainly highlighting a gap in our current knowledge.…”
Section: Emerging Antifungal Drug Resistance In Previously Susceptibl...mentioning
confidence: 99%